More Than Just a Periodontal Pathogen –the Research Progress on Fusobacterium nucleatum - Chen, Yuanxin; Huang, Zhijie; Tang, Zhengming; Huang, Yisheng; Huang, Mingshu; Liu, Hongyu; Ziebolz, Dirk; Schmalz, Gerhard; Jia, Bo; Zhao, Jianjiang (Frontiers in Cellular and Infection Microbiology, 2022)
Fusobacterium nucleatum is a common oral opportunistic bacterium that can cause different infections. In recent years, studies have shown that F. nucleatum is enriched in lesions in periodontal diseases, halitosis, dental pulp infection, oral cancer, and systemic diseases. Hence, it can promote the development and/or progression of these conditions. The current study aimed to assess research progress in the epidemiological evidence, possible pathogenic mechanisms, and treatment methods of F. nucleatum in oral and systemic diseases. Novel viewpoints obtained in recent studies can provide knowledge about the role of F. nucleatum in hosts and a basis for identifying new methods for the diagnosis and treatment of F. nucleatum-related diseases.